MENANAMKAN NILAI NILAI PENDIDIKAN KARAKTER DALAM PROSES BELAJAR MENGAJAR IPS/KN - M. Husen Affan (Universitas Syiah Kuala, 2022)
Character education is a system of inculcating character values to the citizens of the school that includes the components of knowledge, awareness or willingness, and actions to implement those values. Character education can be interpreted as “the deliberate use of all dimensions of school life to foster optimal character development”. In character education in school especially on IPS/Kn learning, All components (stakeholders) must be involved, including the components of education itself, that is, the content of the IPS/Kn curriculum, IPS/Kn learning process and IPS/Kn assessment, Handling or management of subjects, school management, implementation of activities or co-curricular activities, empowerment of infrastructure, financing, and work ethic of all school/neighborhood residents. So with the combination of IPS/PKn learning By instilling character values can be oriented to the formation of the child as a whole human being. The quality of the students becomes superior not only in the cognitive aspect, but also in the character. Children who excel in the character will be able to face all the problems and challenges in life both social environment as the main target of social studies and the environment of the nation and state as the main target of learning Civics (Kn).